Use of tyre wastes into the experimental study of model footings on reinforced soil - Dewaikar, D. M.; Guptha, K. G.; Chore, H. S. (Journal of Structural Engineering, 2024)
Experimental investigations are reported on the study of load-deformation behavior of model square and circular footings in respect of a two-layered system comprising clay as sub-grade and mine waste as a backfill material. The footings were subjected to axial loads. Three different types of reinforcing materials such as Geotextile, Kolon Geo-grid (KGR-40) and Rubber grid derived out of waste tyres were used in the study. The study revealed appreciable increase in ultimate bearing pressure and decrease in settlement with the provision of a single layer reinforcement in respect of both the footings. Further, rubber grid performed better than the Geo-grid and Geotextiles in respect to BCR and SRF. The study indicates significance of solid waste materials such as mine wastes and discarded tyres as effective civil engineering construction materials.